The European fighter aircraft industry : has it lost Asia? - Bitzinger, Richard A. (2012)
Europe’s combat aircraft manufacturers, in losing a potential sale to Japan, could see their future sales to Asia evaporate completely. This could leave the United States in an unassailable position as the world’s predominant fighter aircraft producer.